Pengaruh Online Customer Review Dan Online Customer Rating Terhadap Keputusan Pembelian Konsumen Pada Marketplace Shopee - Riska Sukirman; Fitri Kumalasari; Hendrik (Journal of Trends Economics and Accounting Research, 2023)
This study aims to determine: (1) The influence of online customer reviews on consumer purchasing decisions through the Shopee Marketplace (study on consumers in Poleang District, Bombana Regency, Southeast Sulawesi). (2) The influence of Online Customer Rating on Consumer Purchase Decisions through the Shopee Marketplace (Study on Consumers in Poleang District, Bombana Regency, Southeast Sulawesi). This study uses an approach with quantitative methods. Data collection techniques are primary data and secondary data. The population of this study is all consumers who are in Poleng District, Bombana Regency, Southeast Sulawesi. While the sample of this study amounted to 120 people using accidental sampling technique. Testing the research instrument using the validity test and reliability test with SPSS 25.0. The data analysis technique used in this research is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through measurement model testing (Outer Model) and structural model testing (Inner Model) with SmartPLS 4.0. Based on the research results, it is known that the Online Customer Review variable has a positive and significant effect on Consumer Purchase Decisions as indicated by a P-Values ​​of 0.006 and Online Customer Rating has a positive and significant effect on Consumer Purchase Decisions, this is indicated by a P-Values ​​of 0.004.